THE DEVELOPMENT OF ELECTRONICACCOUNTING BOOK OF SERVICE COMPANIES IN IMPROVING STUDENT ACCOUNTING ABILITY (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2020)
This problem that often occurs in the world of education, especially in vocational high school students, are the difficulties of teaching materials / electronic reference books, teaching materials that are less attractive so students are not interested in reading them, even some students are reluctant to bring textbooks to school because of books it feels thick and heavy to carry everywhere. So that students Have basic knowledge of accounting, especially in accounting services companies only come from the teacher. The purpose of this research is to produce digital literacy in the form of electronic book (e-book) accounting for service companies, Test the effectiveness of using product, and test the attractiveness of service company accounting e-books for Vocational High Schools. This research was conducted using the Research and Development (R&D) research method. The results showed that: 1) The Accounting Services Company e-book developed was considered to be very suitable to be used as a learning resource. This is reviewed based on the results of the validation test assessment (material expert, linguist and media expert) and student responses. 2) Company Accounting Services e-book for Vocational High School students can improve students' accounting abilities. Therefore, the digital teaching materials are effective and accepted 3) There are differences in learning outcomes between students on the initial test and the final test it can be seen from the value of t arithmetic (10.071)> t table (0.679). Thus it can be said there are a significant differences between the average value of students before and after learning by using digital teaching materials (e-books) accounting.